APPLICATION OF SNOWBALL THROWING TO IMPROVE THE LEARNING OUTCOMES OF SOCIAL SCIENCE (IPS) GEOGRAPHY OF STUDENTS IN GRADE VIII C MUHAMMADIYAH 1 JUNIOR HIGH SCHOOL SUKOHARJO IN THE ACADEMIC YEAR 2017/2018 - Andriyah Nurhidayati; Agus Sudargono; Pranichayudha Rohsulina (Universitas Veteran Bangun Nusantara, 2019)
This study aims to improve the learning outcomes of IPS geography through Snowball Throwing cooperative learning methods for students in grade VIII C Muhammadiyah 1 junior hihg school Sukoharjo in the academic 2017/2018. This from of research is classroom action research conducted in two cycles each cycle consisting of two meetings, with four stages of research : Planning, Implementation, Observation and Reflection The subjects of this research were VIII C grade students of Sukoharjo Muhammadiyah 1 Junior High School in the academic year of 2017/2018. With a total pf 21 students. Data collection techniques used were observation, interviews, tests and documentation. The data analysis used in this research was qualitative deaccriptive analysis.The results of this study are to improve the learning outcomes of geography ips social science.This is shown in the learning outcomes of students before and after applying Snowball Throwing model cooperative learning, namely the learning outcomes of students who get KKM scores of 38,09 % increases to 52,38 % in cycle 1 and another increases in cycle 2 to 86,70 % from before. Based on the results of this study it can be concluded that with application of Snowball Throwing Cooperative learning model can improve learning outcomes of IPS geography for students in class VIII C Junior High School Muhammadiyah 1 Sukoharjo in the academic year 2017/2018.